Drosophila mitochondrial transcription factor A (d-TFAM) is dispensable for the transcription of mitochondrial DNA in Kc167 cells. - Goto, A.; Matsushima, Y.; Kadowaki, T.; Kitagawa, Y. (The Biochemical Journal, 2001)
We have cloned cDNA encoding Drosophila mitochondrial (mt) transcription factor A (d-TFAM). RNA interference (RNAi) of d-TFAM by lipofection of haemocyte-derived Kc167 cells with double-stranded RNA reduced d-TFAM to less than 5% of the normal level. Reflecting the ability of TFAM to stabilize mtDNA, RNAi of d-TFAM reduced mtDNA to 40%. Nonetheless, transcription of the ND2 and ND5 genes and their mRNAs remained unchanged for 8 days of the duration of RNAi. We thus show that d-TFAM is not essential for the transcription of Drosophila mtDNA.